Pengaruh Penggunaan Video Sebagai Media Pembelajaran Terhadap Hasil Belajar Tematik Kelas III di SDIT Fathona Palembang - Erfa Astriani; Tutut Handayani; Fuaddilah Ali Sofyan; Sunardi Sunardi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study was to determine whether there is an effect of using video media on thematic learning outcomes in grade III elementary school and of course in the future it can be useful for various parties because the current curriculum is very demanding on the skills and abilities of educators because it improves the quality and quality of current education. This is the main focus of the government's attention. For this reason, using video media is one of the efforts to improve student learning outcomes whether later it is good for use in elementary schools and especially in grade III elementary schools. The research method used by the researcher is quantitative research with the help of SPSS 22. The results show that thematic learning outcomes in class III increase after using video learning media, which means that there is an effect of using video media on teaching and learning activities or thematic learning outcomes in class III, especially in SDIT Fathona Palembang and of course in the future can be applied.